A experiência da família no cuidado à criança com fissura labiopalatina - Martins, Talitha Uliano (Universidade Federal de São Carlos, 2013)
The implications of cleft lip and palate in a child's life go beyond the aesthetic and functional, psychosocial problems may lead not only to her but for the whole family. A satisfactory fitting process depends more on how the family will react and their attitudes, than the presence of the anomaly. The rehabilitation process is experienced by the child and family, and the performance of the Nursing Team happens with them during this journey. The nursing staff participates in training the family for the care, since your formation is also focused on the education of those who attend. This study aims to understand the family's experience across the care of children with cleft lip and palate. This is a clinical-qualitative research and to work with the data used the research narrative. Constitute subjects of the study families of children with cleft lip and palate with up to 3 years old. The data analysis allowed apprehend four themes. Accept and affirm the condition: the news of the presence of cleft lip and palate generates big impact and is a difficult time that the family requires mobilization and adaptation of feelings that result in action to welcome and accept the child. Treading the rehabilitation process: this process begins soon after birth of the child, stretching as its growth, it is long, gradual, exhausting, and suffered implies breaking the routine, trip to the specialist center, extra expenses, surgical procedures, diets, restrictions and cautions. Learn, experiment and adapt care: care of the child with cleft is built through constant experiment. Try positions for feeding, the bottles, the speed of feeding, the formula. In this movement the family adapts and customizes the care to meet the best possible way the needs of your child, and thus the dynamics of everyday life learns to care. Require Informational and Emotional Support: in their trajectory family suffers from lack of supporting information by health professionals, the public and media, feels lonely when they need to find answers for themselves. It is hoped that the discussion of this topic may contribute to understanding the experience of families across the care of children with cleft and enables meet their needs, identify demands and accompanying guidance for the improvement of care provided by health professionals to these families.
Keywords: Enfermagem; Lábio fissurado; Fissura Palatina; Crianças; Família; Cleft Lip; Clet Palate; Child; Family; Nursing; CIENCIAS DA SAUDE::ENFERMAGEM